Respostas
respondido por:
0
y = f(x) = 36 x² - 12x + 1
f(3) = 36(3)² - 12(3) + 1 = 324 - 36 + 1 = 289
f(0,2) = 36(0,04) - 12(0,2) + 1 = 1,44 - 2,40 + 1 = 2,44 - 2,44 = -0,04
*-*-*-*-*-*-*-*-*-*-*-*
06/10/2016
Sepauto
*-*-*-*-*-*-*-*-*-*-*-*
f(3) = 36(3)² - 12(3) + 1 = 324 - 36 + 1 = 289
f(0,2) = 36(0,04) - 12(0,2) + 1 = 1,44 - 2,40 + 1 = 2,44 - 2,44 = -0,04
*-*-*-*-*-*-*-*-*-*-*-*
06/10/2016
Sepauto
*-*-*-*-*-*-*-*-*-*-*-*
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás